Methods of Legal Norms Interpretation by European Court of Human Rights - Палешник, С. І. (Problems of legality, 2015)
The issues that related to the interpretation of European Convention for the Protection of Human Rights and Fundamental Freedoms by European Court of Human Rights are considered in the article. The special attention is given to the interpretation methods that are directly used by Court in his interpretation practice. The examples of such methods applying are also considered in the article.